Traveloka Booking Technology and Customer Satisfaction at Hotel Sahid Using TAM Model - Ardila, Fidha Citra; Wibasuri, Anggalia; Lestari, Winda Rika (Penerbit Goodwood, 2025)
Purpose: This study aims to test how factors in the Technology Acceptance Model (TAM) affect customer satisfaction at Sahid Hotel Bandar Lampung. Methodology: The data source used was primary. Data were collected through a questionnaire randomly distributed to 100 respondents using probability sampling techniques. Data analysis was performed using structural equation Modelling (SEM) with the help of the Smart-PLS application. Results: The results revealed that Perceived Usefulness (PU) had a positive effect on Traveloka’s Attitude Toward Using (ATUs). Perceived Ease of Use (PEOU) has a positive effect on Traveloka’s Attitude Toward Using (ATUs). Enjoyment has a positive effect on Traveloka’s Attitude Toward Using (ATU). Perceived Ease of Use (PEOU) has a positive effect on Traveloka’s Perceived Usefulness (PU). Conclusion: Attitude Toward Using (ATU) has a positive effect on Traveloka’s Behavioural Intention to Use (BI). Behavioural Intention to Use (BI) has a positive effect on customer satisfaction. Perceived Usefulness (PU) has a positive effect on customer satisfaction. Perceived Ease of Use (PEOU) has a positive effect on customer satisfaction. Limitations: To use a larger sample and be able to cover all elements of the population in a balanced manner so that the results of the study can better reflect the actual circumstances and the results can be generalized more broadly. Contribution: Hotel Sahid Bandar Lampung needs to optimize services to consumers. The service is optimized by ensuring security and comfort when transacting on Traveloka.